Ebu Haşim el-Cübbai’nin Zat-Sıfat ilişkisine yaklaşımı: haller teorisi - Güdekli, Hayrettin Nebi (My University, 2008)
EBÛ HÂŞİM el-CÜBBÂÎ’NİN ZÂT-SIFAT İLİŞKİSİNE YAKLAŞIMI: HALLER TEORİSİ Kelâm ilminin temel konularından biri olan ilâhî sıfatlar meselesi hakkında ilk dönem kelâmcıları etraflıca düşünmüş ve bir takım yaklaşımlar geliştirmişlerdir. Bu yaklaşımlar, ilâhî sıfatlar meselesinin anlam alanıyla doğru orantılı olarak “Allah hakkında kullanılan sıfatların O’nda nasıl bulunduğu” (ontolojik problem) ve “Allah’a atfedilen sıfatların nasıl anlaşılması gerektiği” (semantik problem) şeklinde iki problem etrafında toplanmaktadır. İlk dönem kelâmcıları söz konusu iki problemi çözmek maksadıyla bir takım teoriler geliştirmişlerdir. Bu teorilerden biri, Basra Mutezilesi’nin son dönem kelâmcılarından Ebû Hâşim el-Cübbâî’ye aittir. Ebû Hâşim, “ilâhî varlık hakkında kullanılan sıfatların kendisinde nasıl bulunduğu” sorunuyla gündeme gelen “zât-sıfat ilişkisinin nedenselliği problemini” çözüme kavuşturmak amacıyla, haller (ahvâl) teorisini ortaya atmıştır. Ona göre Allah zâtında bulunan ve “vücûd ve adem” ile “kıdem ve hudûs” ile vasıflanamayan bir takım haller sebebiyle sıfatları hak etmektedir. Ebû Hâşim, söz konusu hallerin “mevcûd ve madûm”, “malûm ve meçhûl”, “kadîm ve hâdis” olmadığını söyleyerek Allah’ın zâtında bir takım mevcut manaların kabulünün gündeme getireceği “kadîm varlıkların çokluğu” (teaddüd-i kudemâ) ve “ilâhî zâtın sonradan varlık kazanan şeylere mahal olması” (mahall-i havâdis) gibi problemlerin söz konusu olmamasını sağlamak istemektedir.

ABÛ HASHIM al-JUBBAI’S APPROACH TO THE RELATION OF ESSENCE (ZÂT)-ATTRIBUTE (SIFAT): THE THEORY OF STATES (AHVÂL) The early and classical period theologians thought thoroughly about the problem of the divine attributes, which is the essential subject of the science of Kalam, and they suggested some approaches to this problem. These approaches, being well-proportioned with the framework of the problem of the divine attributes, are concerned with two basic problems, that is, “How are the attributes ascribed to God attributed to Him” (ontological problem) and “How can the attributes ascribed to God be understood when applied to Him?” (semantic problem). The early and classical period theologians suggested some theories to resolve the aforementioned two problems (ontological and semantic). One of the theories belongs to Abû Hâshim al-Jubbâî, who is a theologian in the late period of Basrian School of the Mutazila. Abû Hâshim suggested his theory of states (modes:ahwâl) to find a solution to the difficulty that results from the ontological aspect of the problem of the divine attributes which arose out the problem of “How are the attributes predicated of God ascribed to Him?”. According to Abu Hashim, God pertains the attributes by means of some states which were present at His essence (zât), but which were not qualified by “existence”, “non-existence” and “being eternal” and “coming to being” (hudûs). Abû Hâshim, by proposing that these states (modes) are not “existent” or “non-existent”, neither are they “known” or “unknown”, demanded to drive away the two difficult positions, that is, “the problem of multiple eternal beings” (teaddüdü’l-kudemâ) and “the problem of the existence of contingent beings on the spot of God’s essence” (mahallü’l-havâdis), when one asserts that God has ontologically real attributes.
Keywords: İslam Dini; Kelam